2016
DOI: 10.1371/journal.pone.0154111
|View full text |Cite
|
Sign up to set email alerts
|

Fenretinide (4-HPR) Targets Caspase-9, ERK 1/2 and the Wnt3a/β-Catenin Pathway in Medulloblastoma Cells and Medulloblastoma Cell Spheroids

Abstract: Medulloblastoma (MB), a neuroectodermal tumor arising in the cerebellum, represents the most frequent childhood brain malignancy. Current treatments for MB combine radiation and chemotherapy and are often associated with relevant side effects; novel therapeutic strategies are urgently needed. N-(4-Hydroxyphenyl) retinamide (4-HPR, fenretinide), a synthetic analogue of all-trans retinoic acid, has emerged as a promising and well-tolerated cancer chemopreventive and chemotherapeutic agent for various neoplasms, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(21 citation statements)
references
References 78 publications
(133 reference statements)
2
19
0
Order By: Relevance
“…Cheepala and colleagues showed that ATRA decreased total ERK expression in skin cancer studies [51]. Fenretinide, another retinoid, was found to decrease ERK expression in ONS-76 MB cells [52]. In the current study, total ERK expression was diminished in all 3 MB PDX cell lines following RA or UAB30 treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Cheepala and colleagues showed that ATRA decreased total ERK expression in skin cancer studies [51]. Fenretinide, another retinoid, was found to decrease ERK expression in ONS-76 MB cells [52]. In the current study, total ERK expression was diminished in all 3 MB PDX cell lines following RA or UAB30 treatment.…”
Section: Discussionsupporting
confidence: 54%
“…Fenretinide is active in NB [7][8][9][10] and many other cancer types [11][12][13][14][15][16] by multiple mechanisms, [17][18][19][20][21][22] and it has shown efficacy against cancer stem cells. [23][24][25][26][27][28] Lenalidomide is another alternative antitumor agent currently used in the post-consolidation maintenance therapy of multiple myeloma and other hematological malignances. We selected lenalidomide to combine with fenretinide for its antiangiogenic properties and its acceptable toxicity profile.…”
Section: Introductionmentioning
confidence: 99%
“…[5][6][7][8][9][10][11][12][13] Among the AABMs, fenretinide has a superior pharmacological profile due to its ability to induce cytotoxicity by multiple mechanisms [14][15][16][17][18] and to target cancer stem cell-associated molecular targets. [19][20][21][22] Previous clinical Phase I-III evaluations of fenretinide showed minimal systemic toxicity and good tolerability. 9,23,24 However, clinical trials aimed at evaluating the activity of fenretinide in cancer patients yielded disappointing results, likely due to the low bioavailability of the initial oral capsule formulation.…”
Section: Introductionmentioning
confidence: 99%